2014
DOI: 10.1007/s00415-014-7314-y
|View full text |Cite
|
Sign up to set email alerts
|

Action verb comprehension in amyotrophic lateral sclerosis and Parkinson’s disease

Abstract: Patients with amyotrophic lateral sclerosis (ALS) have a motor disorder and cognitive difficulties, including difficulty with action verbs. However, the basis for the action verb impairment is unknown. Thirty-six participants with ALS and 22 with Parkinson’s disease (PD) were assessed on a simple, two-alternative forced-choice associativity judgment task, where performance was untimed and did not depend on motor functioning. We probed 120 frequency-matched action verbs, cognition verbs, concrete nouns and abst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 27 publications
(42 reference statements)
1
21
1
Order By: Relevance
“…For example, several studies have demonstrated that comprehension of action verbs results in the activation of motor areas in the brain ( Binder and Desai, 2011 , Meteyard et al, 2012 ). Additionally, studies among patients with neurological disorders characterized by motor impairment have systematically found more prominent impairment for verb than noun processing ( Bak and Hodges, 2004 , Fernandino et al, 2013 , York et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, several studies have demonstrated that comprehension of action verbs results in the activation of motor areas in the brain ( Binder and Desai, 2011 , Meteyard et al, 2012 ). Additionally, studies among patients with neurological disorders characterized by motor impairment have systematically found more prominent impairment for verb than noun processing ( Bak and Hodges, 2004 , Fernandino et al, 2013 , York et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Relative deficits with concrete object concepts compared with abstract concepts are found in large series of svPPA patients both in comprehension using lexical stimuli and in narrative expression (Cousins et al 2016, 2017; Hoffman et al 2013). Other examples of relative sensory–motor deficits include difficulty naming and understanding concepts that are associated with motor actions in nonaphasic patients with a neurodegenerative motor disorder known as amyotrophic lateral sclerosis (Grossman et al 2008a, York et al 2014), and reduced comprehension of concepts like ‘thunder’ that depend on auditory feature knowledge in patients who have difficulty with auditory short-term memory (Bonner & Grossman 2012). Note that, because most object concepts do not consist exclusively of visual features, object knowledge may be supported in part by features that are not visual in nature.…”
Section: Semantic Variant Primary Progressive Aphasiamentioning
confidence: 99%
“…Bak, O'Donovan, Xuereb, Boniface, & Hodges, 2001; Boulenger, Mechtouff, Thobois, Broussolle, Jeannerod, & Nazir, 2008;Fernandino et al, 2013a;Fernandino et al, 2013b, but see Kemmerer, Miller, MacPherson, Huber, & Tranel, 2010York et al, 2014). Boulenger et al (2008) found priming effects for action verbs in PD varied as a function of Levodopa uptake (medication improving motor impairment in PD).…”
Section: Methodmentioning
confidence: 99%